Mengidentifikasi Strategi Kaizen untuk Meningkatkan Disiplin dan Produktivitas Mahasiswa di Lingkungan Universitas Buana Perjuangan Karawang (International Forum of Researchers and Lecturers, 2025)
This study aims to identify Kaizen strategies that can be applied to improve student discipline and productivity within Universitas Buana Perjuangan Karawang. Kaizen, a Japanese philosophy of continuous improvement, is considered relevant to encourage positive behavioral change in academic activities and time management among students. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving active students and academic advisors. The results show that applying Kaizen principles such as daily self-evaluation, active involvement in study planning, and the reinforcement of a collective discipline culture significantly contributes to improving academic productivity. This study recommends integrating Kaizen strategies into student development programs to create a more effective and sustainable learning environment.